The Inadequacy of Forrester System Dynamics Computer Programs for Institutional Principles of Hierarchy, Feedback, and Openness. - Hayden, F. Gregory (Journal of Economic Issues, 2006)
The article seeks to discuss the institutional system principles of hierarchy, feedback and openness in order to explain the inadequacy of the Forrester type system dynamics programs to apply those principles. In terms of systems, hierarchies exist to control what events should take place, and to determine when, where and how they should take place. The components of the more powerful level in a structural hierarchy impose directives on the activities and deliveries of other components through different ways to establish kinds of control paths among institutional organizations. Rules, regulations and requirements, which are part of hierarchies, are established in specific social settings to set controls and sanctions that meet normative criteria.